Changes in Blood Concentration of Adenosine Triphosphate Metabolism Biomarkers During Incremental Exercise in Highly Trained Athletes of Different Sport Specializations. Issue 5 (May 2019) - Włodarczyk, Michał; Kusy, Krzysztof; Słomińska, Ewa; Krasiński, Zbigniew; Zieliński, Jacek
Abstract : Abstract: Włodarczyk, M, Kusy, K, Słomińska, E, Krasiński, Z, and Zieliński, J. Changes in blood concentration of adenosine triphosphate metabolism biomarkers during incremental exercise in highly trained athletes of different sport specializations. J Strength Cond Res 33(5): 1192–1200, 2019—We hypothesized that (a) high-level specialized sport training causes different adaptations that induce specific biomarker release dynamics during exercise and recovery and (b) skeletal muscle mass affects biomarker release. Eleven sprinters (21–30 years), 16 endurance runners (18–31 years), 12 futsal players (18–29 years), and 12 amateur runners as controls (22–33 years) were examined. Hypoxanthine (Hx), xanthine (X), uric acid (UA), ammonia (NH3 ), and lactate (LA) concentrations were determined at rest, during an incremental treadmill exercise test (every 3 minutes), and during recovery (5, 10, 15, 20, and 30 minutes after exercise). Hx, X, and UA concentration was determined from plasma, while LA and NH3 from whole blood, and muscle mass was assessed using dual X-ray absorptiometry method. At rest, during incremental exercise, and up to 30 minutes into the postexercise recovery period, sprinters had lowest Hx, X, and UA concentrations, and endurance athletes had lowest NH3 concentrations. For LA during exercise, the lowest concentrations were noted in endurance athletes, except when reaching maximum intensity, where the differences between groups were not significant. There were no significant correlations observed between skeletal muscle mass and biomarker concentration at maximal intensity and recovery in any group. In conclusion, the magnitude of exercise-induced biomarker concentration is only related to training adaptations through specific training profile but not to muscle mass. In addition, the results suggest that combined measuring of LA, NH3, and Hx concentration in blood is useful in indirectly reflecting key changes in exercise- and training-induced energy status. Further research should focus on studying how specific training sessions affect individual biomarker response in highly trained athletes. Abstract : Supplemental Digital Content is Available in the Text.